Simulations of black hole fueling in isolated and merging galaxies with an explicit, multiphase ISM. Issue 4 (3rd October 2022) - Sivasankaran, Aneesh; Blecha, Laura; Torrey, Paul; Kelley, Luke Zoltan; Bhowmick, Aklant; Vogelsberger, Mark; Losacco, Rachel; Weinberger, Rainer; Hernquist, Lars; Marinacci, Federico; Sales, Laura V; Qi, Jia
ABSTRACT: We study gas inflows on to supermassive black holes using hydrodynamics simulations of isolated galaxies and idealized galaxy mergers with an explicit, multiphase interstellar medium (ISM). Our simulations use the recently developed ISM and stellar evolution model called Stars and MUltiphase Gas in GaLaxiEs (SMUGGLE). We implement a novel super-Lagrangian refinement scheme that increases the gas mass resolution in the immediate neighbourhood of the black holes (BHs) to accurately resolve gas accretion. We do not include black hole feedback in our simulations. We find that the complex and turbulent nature of the SMUGGLE ISM leads to highly variable BH accretion. BH growth in SMUGGLE converges at gas mass resolutions ≲3 × 10 3  M⊙ . We show that the low resolution simulations combined with the super-Lagrangian refinement scheme are able to produce central gas dynamics and BH accretion rates very similar to that of the uniform high resolution simulations. We further explore BH fueling by simulating galaxy mergers. The interaction between the galaxies causes an inflow of gas towards the galactic centres and results in elevated and bursty star formation. The peak gas densities near the BHs increase by orders of magnitude resulting in enhanced accretion. Our results support the idea that galaxy mergers can trigger AGN activity, although the instantaneous accretion rate depends strongly on the local ISM. We also show that the level of merger-induced enhancement of BH fueling predicted by the SMUGGLE model is much smaller compared to the predictions by simulations using an effective equation of state model of the ISM.